Comprehensive identification and analysis of circRNAs during hickory (Carya cathayensis Sarg.) flower bud differentiation - Jin, Hongmiao; Yang, Zhengfu; Luo, Jia; Li, Caiyun; Chen, Junhao; Lim, Kean-Jin; Wang, Zhengjia (Frontiers in Plant Science, 2023)
Flower bud differentiation represents a crucial transition from vegetative growth to reproductive development. Carya cathayensis (hickory) is an important economic species in China, with a long juvenile period that hinders its commercial development. In recent years, circular RNAs (circRNAs) have been widely studied and identified as sponges for miRNA regulation of mRNA expression. However, little is known regarding the role of circRNAs in flower buds. In this study, we sequenced circRNAs at three developmental stages (undifferentiated, differentiating, and fully differentiated) in both female and male buds. A total of 6,931 circRNAs were identified in the three developmental stages and 4,449 and 2,209 circRNAs were differentially expressed in female and male buds, respectively. Gene ontology demonstrated that many circRNA host genes participated in various processes, for example, cellular and intracellular pH regulation. Function annotation identified 46 differentially expressed circRNAs involved in flowering regulation, with 28 circRNAs found only in female buds, 4 found only in male buds, and 11 found in both female and male buds. A circRNA-miRNA-mRNA network was predicted based on 13 flowering-related circRNAs and their seven putative interacting miRNAs to describe the regulatory mechanism. Our preliminary results demonstrated a potential involvement of circRNA in bud differentiation. They provided a preliminary theoretical basis for how circRNA might participate in flower development in hickory, perhaps in woody plants.